Three-component synthesis of ynediones by a glyoxylation/Stephens-Castro coupling sequence - Merkul, Eugen; Dohe, Janis; Gers, Charlotte; Rominger, Frank; Müller, Thomas J. J. (Angewandte Chemie. International edition, 2011)
One step back, two steps forward! Starting from diverse heterocycles, the title reaction furnishes ynediones under very mild conditions in a direct and preparatively simple one-pot process. The key to avoiding decarbonylation is the CuI-catalyzed Stephens-Castro alkynylation rather than the usually more efficient Sonogashira coupling. In addition, novel highly atom-economical four-component syntheses of various heterocycles can be achieved.